2014
DOI: 10.1139/apnm-2013-0367
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of a 12-week supervised exercise intervention for colorectal cancer survivors

Abstract: Exercise training improves health-related physical fitness and patient-reported outcomes in cancer survivors, but few interventions have targeted colorectal cancer (CRC) survivors. This investigation aimed to determine the feasibility and efficacy of a 12-week supervised exercise training program for CRC survivors. Feasibility was assessed by tracking participant recruitment, loss to follow-up, assessment completion rates, participant evaluation, and adherence to the intervention. Efficacy was determined by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 48 publications
6
25
2
Order By: Relevance
“…Compared to the findings of Sellar et al (144), the absolute improvement in VO 2 peak of 5.3ml/kg/min reported for the present HIE group may have been due to the higher exercise intensity employed.…”
Section: Cardiorespiratory Fitnesscontrasting
confidence: 96%
See 1 more Smart Citation
“…Compared to the findings of Sellar et al (144), the absolute improvement in VO 2 peak of 5.3ml/kg/min reported for the present HIE group may have been due to the higher exercise intensity employed.…”
Section: Cardiorespiratory Fitnesscontrasting
confidence: 96%
“…The absolute increase in VO 2 peak of 5.3 mL/kg/min for the HIE group in our study is greater than improvements reported previously in colorectal cancer survivors (144). As described by Sellar et al…”
Section: Cardiorespiratory Fitnesscontrasting
confidence: 53%
“…142 Given that it is very rare for young people to have a CRC diagnosis, we can confidently assume that a lower age criterion does not have a decisive influence on eligibility rates. Nine studies (including CRIB) included language restriction as a criterion, 44,49,142,143,145,146,149,150 suggesting a bias towards people who speak a country's first language and thereby potentially limiting generalisability of the study findings to other groups of the population. In CRIB, no patients with CRC were excluded because they were unable to speak English, suggesting that this criterion did not have any bearing on the eligibility rate.…”
Section: Eligibility Ratementioning
confidence: 99%
“…Six studies specifically mentioned that people with metastatic disease would be excluded or only people with local disease would be included. 49,143,145,146,[148][149][150] Thus, there appears to be a bias towards people with early-stage disease, thereby limiting generalisability of findings to people with metastatic disease.…”
Section: Eligibility Ratementioning
confidence: 99%
See 1 more Smart Citation